2017
DOI: 10.1021/acs.chemrev.6b00475
|View full text |Cite
|
Sign up to set email alerts
|

C-Glycopyranosyl Arenes and Hetarenes: Synthetic Methods and Bioactivity Focused on Antidiabetic Potential

Abstract: This Review summarizes close to 500 primary publications and surveys published since 2000 about the syntheses and diverse bioactivities of C-glycopyranosyl (het)arenes. A classification of the preparative routes to these synthetic targets according to methodologies and compound categories is provided. Several of these compounds, regardless of their natural or synthetic origin, display antidiabetic properties due to enzyme inhibition (glycogen phosphorylase, protein tyrosine phosphatase 1B) or by inhibiting ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
123
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 212 publications
(146 citation statements)
references
References 522 publications
(999 reference statements)
2
123
0
7
Order By: Relevance
“…The incorporation of saccharide derivatives into lead compounds represents an attractive approach to diversify drug candidate scaffolds by modulating crucial parameters related to the in vivo efficacy of at herapeutic compound (e.g., solubility,m embrane transport, pharmacodynamics,o rp harmacokinetics). [1] Notably," reverse aryl C-glycosides" [2] comprise ac lass of saccharides that have proven to be efficient antibiotics, [3] antitumor agents, [4] or inhibitors for diabetes. [2d, 5] These glycosides have the particularity of bearing an aromatic moiety directly attached to the carbohydrate through aC À C bond, thus differentiating them from the usual O-glycosides, which leads to better stability to both enzymatic and acidic hydrolysis while preserving excellent biological efficacy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of saccharide derivatives into lead compounds represents an attractive approach to diversify drug candidate scaffolds by modulating crucial parameters related to the in vivo efficacy of at herapeutic compound (e.g., solubility,m embrane transport, pharmacodynamics,o rp harmacokinetics). [1] Notably," reverse aryl C-glycosides" [2] comprise ac lass of saccharides that have proven to be efficient antibiotics, [3] antitumor agents, [4] or inhibitors for diabetes. [2d, 5] These glycosides have the particularity of bearing an aromatic moiety directly attached to the carbohydrate through aC À C bond, thus differentiating them from the usual O-glycosides, which leads to better stability to both enzymatic and acidic hydrolysis while preserving excellent biological efficacy.…”
mentioning
confidence: 99%
“…Several routes toward anomeric,a rylated saccharides have been reported, [2] such as Friedel-Crafts reactions or nucleophilic additions of organometallic reagents (e.g., organolithium or Grignard reagents) to suitable electrophiles. However,s uch methods suffer from serious drawbacks, including harsh acidic or basic conditions,l ow functionalgroup tolerance,a nd undesired side products arising from elimination or epimerization processes.…”
mentioning
confidence: 99%
“…The good inhibitory effect of those compounds was attributed to the hydrogen bond donor ability of the heterocycle, a feature discussed in a recent review. 18 In the context of structure-activity relationships of GP inhibitors, the present results underline the importance of the H-bridge formation since this possibility is absent in the trisubtituted 1,2,4-triazoles. Furthermore, the additional substituent of the triazole ring may also impede binding of these molecules to the active site of the enzyme.…”
Section: Figure 1 Evidence Of the Isomeric Structures For 124-triamentioning
confidence: 52%
“…From the former class several examples of bioactive nucleoside analogues 9 and N 1 - [10][11][12][13] as well as N 4 -glycopyranosides 14 have been known. C-Glycosyl 1,2,4-triazoles are an even more uncommon type [15][16][17][18] and only in recent years has progress been made in this field with the syntheses of 3-glycopyranosyl-5-substituted-1,2,4-triazoles as glycogen phosphorylase inhibitors for potential antidiabetic use. [19][20][21][22][23][24] As a continuation of our efforts in the above syntheses, the preparation of trisubstituted Cglycopyranosyl 1,2,4-triazoles was envisaged to generate molecules for structure-activity relationships of glycogen phosphorylase inhibitors and also for other potential biological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The thio derivatives 9 and 10 were synthesized from the known donor 2,3,4‐tri‐ O ‐acetyl‐5‐thio‐α‐ d ‐xylopyranosyl bromide ( 12 ) (Scheme ). The glycosylation reaction with 2‐naphthol to form 13 turned out to be difficult, due to the formation of C ‐xylosides as the major products resulting from a Fries O→C rearrangement . Praly and co‐workers reported that the structurally similar phenyl 2,3,4‐tri‐ O ‐acetyl‐5‐thio‐β‐ d ‐xylopyranoside is stable below −30 °C, but anomerization as well as rearrangement to the thermodynamically more stable C ‐xyloside occur at 27 °C with a catalytic amount of BF 3 ⋅ Et 2 O .…”
Section: Resultsmentioning
confidence: 99%